Predicting Adverse Childhood Experiences: The Importance of Neighborhood Context in Youth Trauma Among Delinquent Youth. (February 2017) - Baglivio, Michael T.; Wolff, Kevin T.; Epps, Nathan; Nelson, Randy
Few studies have examined multilevel effects of neighborhood context on childhood maltreatment. Less work has analyzed these effects with juvenile offenders, and no prior work has examined context effects of childhood maltreatment through the Adverse Childhood Experiences (ACEs) framework. ACEs include 10 indictors: emotional abuse, physical abuse, sexual abuse, emotional neglect, physical neglect, domestic violence toward the youth's mother, household substance abuse, household mental illness, parental separation/divorce, and household member with a history of jail/imprisonment. Effects of concentrated disadvantage and affluence on ACE scores are examined in a statewide sample of more than 59, 000 juvenile offenders, controlling for salient individual (including family and parenting) measures and demographics. Both disadvantage and affluence affect ACE exposure. Implications for research and policy are discussed.